Campaign issues in the National and Aragonese Press during three elections in Spain: 2011 Local and Autonomous Regional elections, 2011 General elections and 2014 European elections - García Ortega, Carmela; Zugasti Azagra, Ricardo (Anàlisi, 2015)
From a descriptive perspective, this article analyses the presence of campaign issues in the national and Aragonese daily press during the last three elections in Spain: 2011 Local and Autonomous Regional elections, 2011 General elections and 2014 European elections. The objectives of this research are to compare the differences between newspapers and between elections, to identify the main issues, and to ascertain which issues are more recurrent. In order to achieve these goals, quantitative content analysis was applied to 6691 texts published by El País and El Mundo and by the four main daily newspapers edited in Aragon (Heraldo de Aragón, El Periódico de Aragón, Diario del AltoAragón and Diario de Teruel). The results gathered by this research show that, during the three campaigns, the focus of the press centred on issues such as the organization and design of the campaign, electoral participation and abstention, and information about voting intention surveys. Therefore, the press pays more attention to the development of the campaign itself than to the issues that, according to public opinion surveys, are the most important for the citizens. The economic crisis is, however, a very important issue for both the press and Spanish public opinion. In contrast, political corruption, which is considered one of the more prominent issues in surveys, is not highlighted by the newspapers.